Peran Pendidikan Islam Dalam Membentuk Karakter Disiplin Pada Peserta Didik - Hafizah, Naila; Kartika, Wardah Yuni; Ulfani, Sri Mei; Sari, Ratih Kumala; Wismanto, Wismanto (STAI Denpasar Bali, 2024)
This article discusses how Islamic education contributes to the formation of disciplined character in students. Many students in public schools still underestimate aspects of discipline, such as morals, manners and behavior, or others. The aim of this research is to form a disciplined character in students through Islamic education, where Islamic education is a process of deepening and understanding the values ​​of students' knowledge to achieve equality and perfection in life. The method used in this research is a qualitative method with a library approach, collecting sources such as books, journal articles, etc. to be analyzed, then interpreted critically and presented more systematically about the function of Islamic education in the formation of discipline. The results of the research show that the role of Islamic education, including providing religious material, habituation, advice, warnings, and the example of educators, can shape students' disciplined character.